+6282294617836 - Dora Villa Manik; Ma'ruf Tafsin; Armyn Hakim Daulay; Nurzainah Ginting; Hasnudi (Jurnal Peternakan Integratif, 2018)
DORA VILLA MANIK, 2018. "Effectiveness of Gambir Solution (UncariagambirRoxb) on the Performances of Broiler Chickens Infected by Escherichia coli".Supervised by MA'RUF TAFSIN and ARMYN HAKIM DAULAY. Gambir has the potential as an antibacterial which is traditionally used as a drug for diarrhea. This study examines the effectiveness of gambir solution on performance which includes feed consumption, body weight gain, feed conversion and income over feed cost (IOFC) in broiler chickens infected with E. coli. It was held in November - December 2017 at the Laboratory of Biology, Animal Husbandry Study Program, Faculty of Agriculture University of Sumatera Utara, using a completely randomized design (CRD) with 6 treatments and 3 replications. The treatment consisted of P0A = without infection and without treatment, P0B = infection with E. coli and P1, P2, P3, respectively E. coli infection + Gambir solution 2%, 4%, 6% and P4 = E. coli + infection Tetracycline antibiotics. The results showed that the administration of gambir solution at a dose of 2% - 6% was significantly (P<0.05) effective in improving the performances of broiler chickens infected with E.coli and able to compensate for the use of commercial antibiotics in the form of tetracycline. The highest IOFC is in the 4% gambir solution.